Nuclear medicine technology for diagnosisof neuroendocrine tumors - D. V. Ryzhkova; D. N. Тikhonova; E. N. Grineva (Сибирский онкологический журнал, 2016)
This article is the review of issues of the literature for the past 10 years and is dedicated to the analysis of the radiopharmaceuticals and efficacy of the novel nuclear medicine technologies for the diagnosis, staging and prognosis of neuroendocrine tumors. Diagnostic efficacy of a scintigraphy and a positron emission tomography for detection of gastroenteropancreatic and lung carcinoid, medullary thyroid cancer, pheochromocytoma and haraganglioma and choice of radiopharmaceuticals were demonstrated by the results of the clinical studies. The causes of false positive and falce negative results were specified.